Combining e-books with mind mapping in a reciprocal teaching strategy for a classical Chinese course. (January 2018) - Wu, Ting-Ting; Chen, An-Chi
Abstract: Chinese texts contain the essence of traditional Chinese culture and humanistic spirit, although they are obscure and difficult to understand. The integration of e-books into language learning can play a positive role and improve reading comprehension because of the diversified support tools and features of multimedia interaction in e-books. Therefore, this study investigated the teaching of classical Chinese with a combination of e-books, reciprocal teaching, and mind mapping; the effects of this approach on reading comprehension and knowledge sharing were explored. The sample consisted of two tenth-grade classes of a vocational school. Both groups received the reciprocal teaching strategy with mind mapping. The control group received traditional paper books; the experimental group received e-books. Quantitative and qualitative analyses were used in this study. The results were as follows. (1) Classical Chinese reading comprehension aspect: The experimental group performed more satisfactorily than did the control group, indicating that the integration of the e-book resulted in this measurable improvement by enhancing learners' reading comprehension. (2) Knowledge sharing aspect: The pretest and posttest scores significantly differed between the experimental and control groups, indicating that diversified support tools can promote knowledge sharing. (3) Mind-mapping aspect: the scores of the whole structure (color and image), association skills, and the contents of the articles were more satisfactory in the experimental group than in the control group. (4) Learners had a positive attitude toward the combination of e-books, reciprocal teaching, and mind mapping. Highlights: Classical Chinese combination with e-books, reciprocal teaching, and mind mapping. Diversified support tools in e-books can promote knowledge sharing. Learners had a positive attitude toward this teaching strategies. The learners drew more informative mind maps on the e-books. The e-books significantly improved reading comprehension of classical Chinese.